Una sintesi della storia del Seminario di Milano dagli studi e dalle ricerche di A. Rimoldi - Dell’Orto, Umberto (La Scuola Cattolica, 2025)
In reviewing the studies of A. Rimoldi, is given a map to orient the reader in the knowledge of the entire history of the Seminary of Milan. The author outlines the parties better managed and the weakest of the indicative map, with a focus on bringing the reading keys proposed by A. Rimoldi. Thanks to methodological information and access to sources, this study suggests further research developments.